The Ninth Buddha - Easterman, Daniel (London Grafton Bools, 1988)
An international thriller in the classic tradition by the author of "The Seventh Sanctuary", this story follows the trail of murder and mystery initiated by the kidnapping of a young man. His father's search leads him to Mongolia and an encounter with the goddess Chindamani.
Keywords: Himalaya Mountains -- British